Migration policy uncertainty and stock market investor sentiment - Beyza Mina Ordu-Akkaya (Journal of Capital Markets Studies, 2018)
Purpose - The purpose of this paper is to examine the volatility transmission between migration policy uncertainty indices (MI) of France, Germany, UK and the USA, and respective stock markets of these countries. Therefore, the author’s major intention is to understand whether MI is a critical factor affecting company valuations and investor sentiment. Design/methodology/approach - The author proxies volatility via EGARCH (1,1) for all series and employs Diebold–Yilmaz (2012) methodology to test the spillover, which is a simple yet very intuitive procedure. This method allows one to analyze the numerical amount of spillover, as well as the direction. Findings - Findings propose that volatility transmission is from migration index to stock markets for the UK and US markets, but similar findings are not applicable for France and Germany. However, when cross-market transmissions are analyzed, it is observed that migration policy uncertainty of US spills significant volatility to all European stock markets. Hence, the findings underline the central role of US markets. Originality/value - Given the increasing worries about migration across the USA and Europe, the author tries to cast light on whether investor sentiment alters by migration policies. The literature is recently building and best of the author’s knowledge; the paper is the first to investigate the cross-country spillover between MIs, which has not been performed before.